Modulation of opioid pharmacokinetics and pharmacodynamics, in vivo - Elkiweri, Iman, author; Tissot van Patot, Martha, advisor; Wagner, Anne E., committee member; Miller, Charles W., committee member; Ishi, Douglas N., committee member; Bowen, Richard A., committee member (Colorado State University. Libraries, 2005)
Inter-individual variability in response to opioid anesthesia complicates optimal and effective anesthetic management. Extensive first-pass pulmonary uptake of opioids has a significant impact on the central effect. Because a greater understanding of the mechanisms controlling opioid transport into the lung and brain is essential to developing dosage strategies, we investigated the role of opioid transport inhibitors in lung and brain of Sprague Dawley rats using pharmacokinetic and pharmacodynamic modeling techniques. First, we evaluated the effect of verapamil, a P-glycoprotein (P-gp) efflux transporter inhibitor, on fentanyl and loperamide partitioning in lung (PL) and brain (PB) and central effect by a continuously processed electroencephalogram (EEG), in vivo and hypothesized differential effects of verapamil on these processes. Our results showed that verapamil slightly decreased PB for fentanyl, whereas PL and PB of loperamide increased to a much larger extent. Central effect was reduced with verapamil-induced reduction of fentanyl PB, while verapamil increased loperamide central effect. Also, this is the first report of loperamide crossing the blood brain barrier and eliciting a central effect. We then investigated the effect of opioids on verapamil disposition in lung and brain, in vivo. We found that fentanyl slightly reduced verapamil PB but slightly increased PL; in contrast, loperamide increased PL and PB. These results confirm that verapamil and loperamide are substrates of the efflux transporter P-gp and suggest that verapamil and fentanyl may be substrates of an as yet unidentified inward transporter. Because our study showed that verapamil had only slight effect on fentanyl partitioning and clearance, we hypothesized that inhibition of uptake by organic anion transport polypeptides (Oatp) using pravastatin or naloxone may reduce PL and PB of fentanyl, in vivo. We report that coadministration of fentanyl with pravastatin or naloxone reduces PL and PB of fentanyl in Sprague Dawley rats. In conclusion, Oatp inhibition modulates fentanyl lung and brain concentration; whereas loperamide concentrations in lung and brain are closely controlled by P-gp.
Keywords: anatomy and physiology; animals; pharmacology